Gravitational solitons - Belinski, V. (Vladimir), 1941- (Cambridge monographs on mathematical physics., 2001)
This is the first book to give a self-contained exposition of the theory of gravitational solitons and provide a comprehensive review of exact soliton solutions to Einstein's equations. A valuable reference for researchers and graduate students.